The effect of a transfer program for the elderly in Mexico City on co-residing children's school enrollment - Emilio Gutierrez; Laura Juárez González; Adrian Rubli (Banco de México, 2015)
This paper studies whether the increase in government transfers, induced by an old-age pension program for individuals age 70 and older in Mexico, affects co-residing children's school enrollment, using a regression discontinuity analysis. Results suggest that while household composition and other household-level characteristics do not change significantly at the cutoff age for program eligibility, co-residing children's school enrollment increases significantly. This suggests that public resources for older adults might generate benefits for other age groups. An additional finding is that the increase in school enrollment takes places mostly at the program eligibility cutoff and not before. Given that the program transfer is known and potentially anticipated by individuals who are only a few years away from being eligible, this suggests that households might have credit constraints.
Keywords: J14; I25; 330; government transfers; school enrollment